Psychological and pedagogical support of the future social work specialist’s professional development - M.G., Sergeeva; T.G, Stanchuliak; L.K., Serova; E.G., Khvorikova; E.F., Shaleeva (Opción, 2019)
This arThe article focuses on the issue of psychological and pedagogical support in the professional growth of a social worker via a comparative qualitative research method. As a result, the essential premise for the professional development of a social worker is the possibility to choose ways of professional self-realization in the ambiguity zone and the necessity of the certainty zone existence. In conclusion, the model creates premises for the effective realization of the continuity principle as it characterizes the nature of the actual development zone and focuses on the proximal development zone.